Minimally invasive sleeve lobectomy for centrally located lung cancer: A real-world study with propensity-score matching - Chen, Tangbing; Zhao, Weigang; Ji, Chunyu; Luo, Jizhuang; Wang, Yiyang; Liu, Yuan; Weder, Walter; Fang, Wentao (Frontiers in Oncology, 2023)
Background: The safety, feasibility, and prognosis of sleeve lobectomy by minimally invasive surgery (MIS) remain to be validated. The purpose of this study was to investigate outcomes in real-world patients receiving minimally invasive sleeve lobectomy in a balanced large cohort. Methods: Between January 2013 and December 2018, 578 consecutive patients undergoing sleeve resection at a high-volume center were retrospectively analyzed. Surgical and oncologic outcomes were compared between MIS and thoracotomy patients after propensity-score matching (PSM). Results: MIS sleeve lobectomy was increasingly used as a time-trend in real-world. Before PSM, the MIS group had smaller tumor size, more T2-stage cases, and more right upper lobe sleeve lobectomies compared to the Open group. After 1:4 PSM by patient demographics and tumoral characteristics, 100 cases of MIS and 338 cases of Open sleeve lobectomy were further analyzed. Although median operation time was longer in the MIS group than in the Open group (170.5 minutes vs.149.5 minutes, P < 0.001), patients in MIS group had significantly less estimated intraoperative blood loss (100 ml vs. 200 ml, P = 0.003), shorter drainage duration (5 days vs. 6 days, P = 0.027) and less amount of drainage (1280 ml vs. 1640 ml, P < 0.001) after surgery. Complete resection rate, combined angioplasty, number of dissected lymph nodes, post-operative length of stay, postoperative morbidity and mortality rate, and application of adjuvant therapy were similar between the two matched groups. Conversion to open thoracotomy was necessary in 13.6% patients, but with similar perioperative outcomes compared to Open cases except for longer operation time. More lower lobe sleeve lobectomies were accomplished via robot-assisted thoracoscopic surgery than via video-assisted thoracoscopic surgery (40.0% vs. 12.0%, P = 0.017) in MIS patients. Five-year overall survivals (MIS vs. Open: 72.7% vs. 64.4%, P = 0.156) and five-year progression-free survivals (MIS vs. Open: 49.2% vs. 50.5%, P = 0.605) were similar between the two matched groups. Conclusions: MIS sleeve lobectomy is associated with similar or even better perioperative results and oncologic outcomes to open thoracotomy. Conversion to thoracotomy does not compromise perioperative outcomes. Robot surgery may be preferable for more complex sleeve resections.